A Cross-Country Study of Cigarette Affordability and Single-Stick Purchases Using Survey Data From African Countries - Filby, Samantha (MEDLINE - Academic, 2024)
Abstract INTRODUCTIONReducing cigarette affordability is paramount for reducing cigarette consumption. Measuring affordability requires data on cigarette prices. Unlike the commonly used retail price of a 20-pack of the most-sold cigarette domestically, survey-derived cigarette prices reflect differences arising from the brand variety and the types of packaging in which cigarettes are purchased.AIMS AND METHODSThis paper uses self-reported cigarette price data from the eight African countries that have implemented the Global Adult Tobacco Survey (GATS) to construct country-level Relative Income Prices. The relationship between cigarette affordability, cigarette smoking prevalence, and cigarette smoking intensity, is examined using logit models for smoking participation (N = 51 122) and generalized linear models for conditional cigarette demand (N = 2443). GATS data are also used to produce nationally representative estimates of the prevalence of single-stick cigarette purchases in the sampled countries.RESULTSThe estimated affordability elasticity of cigarette smoking participation is -0.245 (95% CI = -0.411 to -0.078). The estimated affordability elasticity of smoking intensity is -0.155 (95% CI = -0.286 to -0.023). Single-stick cigarette sales dominate all-markets. The proportion of smokers who reported buying cigarettes in the form of single sticks during their most recent cigarette purchase exceeds 90% in Kenya, Tanzania, and Uganda.CONCLUSIONSThe results point to the need for governments in the countries sampled to increase excise taxes in a manner that renders cigarettes less affordable over time, and to enact and enforce legislation that prohibits the sale of single cigarettes. These findings highlight that measures to reduce both the demand and supply of cigarettes will be required to reduce their use in the region.IMPLICATIONSThis study is the first to examine the prevalence of single-stick cigarette purchases, and the association between cigarette affordability and smoking outcomes, in the African setting, using data from the GATS. Findings provide local evidence for the countries sampled, which represent over half of sub-Saharan Africa's adult population (aged 15 and older), on the importance of implementing excise tax increases that reduce cigarette affordability over time. They also highlight the need to enact and enforce legislation that prohibits the sale of single cigarettes.
Keywords: Cigarette ; Affordability; Single-Stick Purchases; Survey Data From African Countries